Intermittent Explosive Disorder - Çetin Demirtaş, Sinem; Sabahi, İrem Sanem and Tamam, Can Tuna and Demirkol, Mehmet Emin and Tamam, Lut (Scientific Reports in Medicine, 2024)
Intermittent explosive disorder is characterized by recurrent episodes of inability to resist aggressive impulses, resulting in damage to other people or other people’s property. In the history of DSM, it first appeared as ’isolated explosive disorder’ in DSM-III. However, with some changes in the diagnostic criteria, it is included under the title of ’destructive, impulse control and conduct disorders’ in DSM-5. Although previous studies have shown it is a rare disorder, recent epidemiological studies suggest it may be more common than thought. For this reason, it is essential to master the clinical features and learn the treatment methods in order to recognize people with this disorder and apply the appropriate treatment.